IMPACT OF FLAXSEED INCLUSION IN DAMASCUS GOAT'S RATION ON DIGESTIBILITY, SOME BLOOD PARAMETERS AND REPRODUCTIVE PERFORMANCE - M. Meteab; H. El-Sayed; Abeer EL-Essawy; M. Nassar; N. El-Bordeny (Arab Universities Journal of Agricultural Sciences, 2018)
Feeding flaxseed to dairy animals improve milk production and reproductive performance. So, the objective of our study was to investigate effect of inclusion flaxseed in Damascus goat's ration on its reproductive performance. Twenty-four Damascus goats (31.40 ±0.50 kg weight and 2-3 years old) were divided into three groups (randomly, eight animals each). The basic diet of  control group (T1) consisted of 56.67% concentrate feed mixture (CFM) and 33.33% Alfalfa hay, while the groups T2 and T3 supplemented with 10% full fat soya, 5% flaxseed + 5% full fat soya and 10% flaxseed, respectively. Inclusion flaxseed in goat’s ration at rate of 5 and 10% resulted in significant increase in all nutrients digestibility, except nitrogen free extract digestibility (NFE) as well as the nutritive values as total digestible nutrients (TDN). Dry matter intakes (DMI) of the different experimental groups were comparable. Goats in T3 recorded the highest does conceived, twinning, conception and kidding rates % as well as total kids born, than other groups (T1 and T2). On the hand T3 recorded the lowest aborted does and barren does (Zero) compared to T1 and T2. Animals of T3 recorded significant higher of total protein, globulin, Albumin and urea concentration than T1 and T2. Concerning lipids profile, the animals of T3 recorded significant lower triglycerides, cholesterol and Low-density lipoprotein concentration than those of T1 and T2. While the animals of T3 recorded significant higher High-density lipoprotein concentration compared to  T2 and T1. The body weight of does is not significantly affected by any of three treatments. In conclusion, flaxseed supplementations in Damascus goat's diets during the gestation period lead to improve total tract digestibility, reduced blood lipids and normalize renal and hepatic functions and improved its reproductive performance, especially those fed on diets containing 10% flaxseed.